Egypt as utopia: on Isocrates’ ‘Busiris’ and its possible relation to Plato’s political thought - Hernández de la Fuente, David (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2013)
During the 5th and 4th centuries BC, Egypt was a kind of conceptual mirror for the Greeks whenever they should speak of history, science or religion, and this is especially evident regarding the debate about the best form of government. The government of sages or priests, two of the utopian ideas most fi rmly rooted in Greek thought, fi nds a mythical basis in Egypt. This contribution aims to study the speech Busiris, by Isocrates, and its possible relationship with the Platonic projects of the Republic and, especially, the Laws. We will analyze the image of Egypt as an Utopian mirror and the various approaches to the historical and literary context of the relation bewteen Isocrates and Plato, from irony to political-philosophical proposals.
Keywords: Busiris; Isocrates; Plato; Laws; Classical Political Theory; Ancient Utopia